Biochemical and structural characterization of murine GBP7, a guanylate binding protein with an elongated C-terminal tail. Issue 21 (5th November 2019) - Legewie, Larissa; Loschwitz, Jennifer; Steffens, Nora; Prescher, Martin; Wang, Xue; Smits, Sander H. J.; Schmitt, Lutz; Strodel, Birgit; Degrandi, Daniel; Pfeffer, Klaus
Abstract: Guanylate-binding proteins (GBPs) constitute a family of interferon-inducible guanosine triphosphatases (GTPases) that are key players in host defense against intracellular pathogens ranging from protozoa to bacteria and viruses. So far, human GBP1 and GBP5 as well as murine GBP2 (mGBP2) have been biochemically characterized in detail. Here, with murine GBP7 (mGBP7), a GBP family member with an unconventional and elongated C-terminus is analyzed. The present study demonstrates that mGBP7 exhibits a concentration-dependent GTPase activity and an apparent GTP turnover number of 20 min −1 . In addition, fluorescence spectroscopy analyses reveal that mGBP7 binds GTP with high affinity ( K D  = 0.22 µM) and GTPase activity assays indicate that mGBP7 hydrolyzes GTP to GDP and GMP. The mGBP7 GTPase activity is inhibited by incubation with γ-phosphate analogs and a K51A mutation interfering with GTP binding. SEC-MALS analyses give evidence that mGBP7 forms transient dimers and that this oligomerization pattern is not influenced by the presence of nucleotides. Moreover, a structural model for mGBP7 is provided by homology modeling, which shows that the GTPase possesses an elongated C-terminal (CT) tail compared with the Caa X motif-containing mGBP2 and human GBP1. Molecular dynamics simulations indicate that this tail has transmembrane characteristics and, interestingly, confocal microscopy analyses reveal that the CT tail is required for recruitment of mGBP7 to the parasitophorous vacuole of Toxoplasma gondii .